USING CHILDREN SHORT STORIES TO ENHANCE STUDENTS` READING COMPREHENSION - Merli Puji Handayani (Journal of English and Education, 2013)
The study informs the use of children short stories in teaching reading comprehension in one of junior high schools in Bandung. Due to their length, vocabulary, and storyline, children short stories were selected for the purpose to increase students’ motivation to read. A classroom action research was conducted in this study in form of three cycles of treatment. The data were collected through various sources: observation sheet, reading test, questionnaire, and interview. The data then were analyzed through triangulation method and reported in qualitative descriptive analysis. The findings revealed despite some limitations, the use of children short stories helped the students to improve their reading comprehension. The result of reading test showed a slightly improvement on the students’ average score from 61.09 in diagnostic test increased to 76.28 in Cycle 3 therapeutic test. The result of observation implied that the employment of reading strategies and the characteristic of children short stories gave influences to the improvement of students’ reading comprehension. In addition, the results from questionnaire and interview indicated that students were aware of having progress in terms of vocabulary and comprehending the text generally. It is thus recommended for further studies to minimize the challenge found in this study and to vary kinds of children short stories used. Keywords: A model of teaching, children short stories, reading comprehension, EFL students